The Renin-Angiotensin System in the Development of Salt-Sensitive Hypertension in Animal Models and Humans - Beate Rassler (MDPI AG, 2010)
Hypertension is still one of the major causes of death from cardiovascular failure. Increased salt intake may aggravate the rise in blood pressure and the development of consequential damage of the heart, the vessels and other organs. The general necessity of restricted salt intake regardless of blood pressure or salt sensitivity has been a matter of debate over the past decades. This review summarizes the main pathogenic mechanisms of hypertension and salt sensitivity in rat models, particularly in the spontaneously hypertensive rat (SHR), and in patients with essential hypertension (EH). Although SHRs are commonly considered to be salt-resistant, there is much evidence that salt loading may deteriorate blood pressure and cardiovascular function even in these animals. Similarly, EH is not a homogenous disorder - some patients, but not all, exhibit pronounced salt sensitivity. The renin-angiotensin system (RAS) plays a key role in the regulation of blood pressure and salt and fluid homeostasis and thus is one of the main targets of antihypertensive therapy. This review focuses on the contribution of the RAS to the pathogenesis of salt-sensitive hypertension in SHRs and patients with EH.